Review: Preparation of Flavonoid Nanoparticles using the Nanoprecipitation Method - Pratama, Rizky Farhan; Sopyan, Iyan; Rusdiana, Taofik (Universitas Padjadjaran (Unpad), 2022)
Flavonoids are polyphenolic compounds that have 15 carbon chains, 2 benzene rings and a heterocyclic pyran ring. From the literature study, it is known that flavonoids have various pharmacological activities such as anticancer, antimicrobial, antiviral, antiangiogenic, antimalarial, antioxidant, neuroprotective, antitumor, and antiproliferative agents. However, flavonoids have limited oral bioavailability which may be due to their poor solubility, low permeability, and low stability, which impair their effectiveness as therapeutic agents. One of the efforts to increase solubility is nanoparticle technology where the active compound particles are reduced to the nanometer scale, usually up to 100 nm. Nanoprecipitation is a method of preparing nanoparticles by dissolving the active drug substance and polymer into an organic solvent and then adding an anti-solvent such as water. The advantages of this method are the production is relatively fast, inexpensive, does not require a lot of energy, and does not require emulsion precursors. The purpose of this literature review is to examine the technique of making flavonoid nanoparticles using the nanoprecipitation method, the results of their characterization and evaluation. Based on a literature review that has been carried out on 30 journals, there are 20 flavonoid secondary metabolites that have been prepared into nanoparticles using the nanoprecipitation method. Some of the polymers used were effective in achieving satisfactory particle size, polydispersity index (PDI), Zeta potential and Encapsulation Efficiency (EE%). Thus, the nanoprecipitation method can be used to make flavonoid nanoparticles with optimal formulations to improve the physicochemical properties of flavonoids for drug development in the future.